PENINGKATAN KREATIVITAS PESERTA DIDIK MELALUI TEKNIK MENCETAK DENGAN MEDIA PELEPAH PISANG DI DESA TRUNAMANGGALA - Aini, Ani Nur; Kuswandi, Aos (An-Nizam, 2024)
Art is one part of the world of education that can be a means that can be used to develop the creativity of students. graphic arts is one form of encouraging students' creativity in art such as using banana leaf as a form of utilizing natural materials around in making students creative to create a graphic art such as batik. this is one of the importance of implementing a program to increase students' creativity through printing techniques with banana leaf media. The purpose of this community service is to utilize natural resources and improve creativity skills for students. This community service method uses a community education model through a graphic arts education approach. The results of this community service show the enthusiasm of students towards community service activities at elementary schools in Trunamangga Village, Cimalaka District, Sumedang Regency, where students when doing art activities printing banana leaf media show a very good and pleasant response.